Ethiopian Orthodox Christianity in a Global Context Entanglements and Disconnections - Paulau, Stanislau; Tamcke, Martin (Texts and Studies in Eastern Christianity, 2022)
This volume offers a new perspective on the Horn of Africa's Christian past and reclaims its place on the map of global Christianity.